Misleading good students - Arató, Ferenc; Szerpák, Tünde (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In this study, we present the fi rst results of a comprehensive research. The aim of the research is to examine what expectations are covered in terms of thinking skills by the state-commissioned learning-teaching aids, including, for example, the summative thematic tests on history at the primary school level. Each element of the original model of Bloom’s taxonomy used for the study can be identifi ed by an element of the 2012 Hungarian National Curriculum and the 2020 Hungarian National Curriculum output expectations. Therefore, we can use Bloom’s taxonomy to determine what cognitive domains the papers cover and provide feedback on the performance of the learners. The first results of the study show that the final tests mostly include tasks in the cognitive dimension related to memorizing and, to a lesser part, to understanding. Thus they do not provide feedback on all the output requirements expected in the 2012 and 2020 Hungarian National Curricula concerning the different cognitive domains.